The effectiveness of cognitive-behavioral therapy in alleviating COVID-19-related anxiety, fear of negative evaluation, and depression among women diagnosed with anorexia nervosa - Farzin Bagheri Sheykhangafshe; Vahid Savabi Niri; Shabnam Baryaji; Fatemeh Eghbali; Ali Fathi-Ashtiani (حیات, 2023)
Background & Aim: Eating disorders manifest numerous psychological and social consequences for both individuals and society. The present study was conducted to investigate the effectiveness of cognitive-behavioral therapy in alleviating COVID-19-related anxiety, fear of negative evaluation, and depression among women diagnosed with Anorexia Nervosa. Methods & Materials: This study employed a quasi-experimental pre-test-post-test design with a control group. The research population consisted of women diagnosed with anorexia nervosa in Tehran in 2022. Thirty participants were selected through convenience sampling from psychological clinics in the 6th and 8th districts of Tehran, and were randomly assigned to either the intervention group (n=15) or the control group (n=15). Questionnaires assessing eating attitudes, COVID-19-related anxiety, fear of negative evaluation, and depression were administered to both groups. The intervention group received a total of eight 90-minute sessions of cognitive-behavioral therapy, while the control group did not receive any intervention. The collected data were subsequently analyzed using multivariate analysis of covariance through the SPSS software version 24. Results: The results of the study showed that cognitive-behavioral therapy led to a significant reduction in mental anxiety related to COVID-19 (P<0.001, F=36.41), physical anxiety related to COVID-19 (P<0.001, F=39.15), fear of negative evaluation (P<0.001, F=41.92), and depression (P<0.001, F=47.48) in women diagnosed with anorexia nervosa (P<0.001). Conclusion: Cognitive-behavioral therapy demonstrated efficacy in alleviating psychological disorders among women diagnosed with anorexia nervosa. Given the potentially severe impairment of mental health experienced by numerous individuals with anorexia nervosa, it is imperative to implement measures for identifying and providing psychological interventions to vulnerable groups.